2001
DOI: 10.1093/hmg/10.3.291
|View full text |Cite
|
Sign up to set email alerts
|

Gentamicin-mediated suppression of Hurler syndrome stop mutations restores a low level of alpha-L-iduronidase activity and reduces lysosomal glycosaminoglycan accumulation

Abstract: Hurler syndrome is the most severe form of a lysosomal storage disease caused by loss of the enzyme alpha-L-iduronidase (encoded by the IDUA gene), which participates in the degradation of glycosaminoglycans (GAGs) within the lysosome. In some populations, premature stop mutations represent roughly two-thirds of the mutations that cause Hurler syndrome. In this study we investigated whether the aminoglycoside gentamicin can suppress stop mutations within the IDUA gene. We found that a Hurler syndrome fibroblas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
96
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(101 citation statements)
references
References 31 publications
3
96
1
1
Order By: Relevance
“…In the last few years, other potential strategies such as pharmacological chaperones [8], or the suppression of pathogenic nonsense mutations through the induction of translational readthrough have emerged [2,[9][10][11][12][13][14][15][16][17][18]. To this effect, aminoglycoside antibiotics such as gentamicin [16,17], and small molecules such as PTC124 [18] and NB84 [19], have been described to induce PTC readthrough, eluding the NMD mechanism and allowing the formation of stable mRNAs encoding for full-length mutant, but probably still quite active, proteins [20,21]. These products reduce proofreading of codon-anticodon recognition in the ribosome, allowing the suppression of PTCs and, as a general rule, the insertion of glutamine or tryptophan at premature UAG/UAA or UGA codons, respectively, occurs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, other potential strategies such as pharmacological chaperones [8], or the suppression of pathogenic nonsense mutations through the induction of translational readthrough have emerged [2,[9][10][11][12][13][14][15][16][17][18]. To this effect, aminoglycoside antibiotics such as gentamicin [16,17], and small molecules such as PTC124 [18] and NB84 [19], have been described to induce PTC readthrough, eluding the NMD mechanism and allowing the formation of stable mRNAs encoding for full-length mutant, but probably still quite active, proteins [20,21]. These products reduce proofreading of codon-anticodon recognition in the ribosome, allowing the suppression of PTCs and, as a general rule, the insertion of glutamine or tryptophan at premature UAG/UAA or UGA codons, respectively, occurs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Gentamicin binds with cell wall phospholipids, obstructing the chain reactions of phosphotidyl inositol which impairs cell admired. It results by production of reactive oxygen species (ROS) 5 . The strategies aimed at ameliorating the nephrotoxicity are of clinical interest 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Gentamicin has been investigated as a read-through agent for MPS I (Keeling et al 2001;Hein et al 2004), and this aminoglycoside has the capacity to cross the bloodbrain barrier. Aminoglycosides are 2-deoxystreptamine derivatives, which can be modified by links at the 4, 5, or 6 positions.…”
Section: Discussionmentioning
confidence: 99%
“…In a preclinical study using cultured cells, we demonstrated that gentamicin enhanced the read-through of IDUA premature stop codons and induced the synthesis of significant amounts of active a-L-iduronidase (Keeling et al 2001;Hein et al 2004). Aminoglycosides such as gentamicin can induce ribosomal read-through, by binding to the eukaryotic ribosome, causing a conformational change that induces faulty stop codon recognition (Francois et al 2005).…”
Section: Introductionmentioning
confidence: 99%